Comparing Study of Different Dielectric Materials on the Electrical Discharge Plasma Generation and its Application for Seed Germination Improvement - MUHAMMAD AFIFI BIN ABDUL JAMIL,; NORAIN BINTI SAHARI, (Progress in Engineering Application and Technology, 2024)
This thesis aims to improve applications in industrial, helpful, and environmental domains through investigating the effects of two dielectric materials, glass and quartz, on the production and properties of dielectric barrier discharge (DBD) plasma. The non-thermal DBD plasma is produced by passing a high voltage across the dielectric barrier that use copper tape as the electrodes. An important factor influencing the properties and effectiveness of plasma creation is the dielectric material. This lack of information may prevent DBD plasma systems from being optimized and modified for certain uses including surface treatment, ozone generation, and plasma medicine. The aim of this research is to methodically examine how the dielectric materials quartz and glass affect the creation and properties of DBD plasma. Through the analysis of these materials' effects. To be able to achieve this, the study proceeded to build a DBD plasma system using a 50 Hz, 240 V Neon Transformer power supply, and investigate the effects of quartz and glass dielectric materials on the production of DBD the plasma; and assess the effectiveness of DBD plasma produced through different dielectric materials to improve mung bean seed germination. The process comprised building a plasma generating chamber with a junction box and comparing the dielectric materials' plasma start and maintenance characteristics through experiments. In contrast to quartz, which had plasma initiation at 1.70 kV and intensified at 2.98 kV, glass had plasma initiation at 1.04 kV and intensified at 2.38 kV. These results suggest that quartz, in comparison to glass, sustains more intense plasma at higher voltages but requires a greater voltage for plasma initiation due to its higher dielectric constant and thermal conductivity. In comparison to glass, quartz was shown to be a better dielectric material. It produced a more consistent and intense plasma, which successfully accelerated the germination of mung bean seeds. These discoveries advance environmental science, medicine, and business by facilitating the efficient design and optimization of DBD plasma systems for many kinds of uses.